IMPROVING THE TECHNOLOGY OF EXTRA VIRGIN PEACH KERNEL OILS - Ye. Kotliar; B. Iegorov; N. Dets; D. Skrypnichenko; L. Lanzhenko (Harčova Nauka ì Tehnologìâ)
The possibility of using the peach stone kernels of varieties ‘Cardinal’, ‘Nectarine’, ‘Flamingo’ and ‘Moldavian’ as a promising raw material for the production of oil and fat products was investigated. The peach kernels were characterised and it was found that the oil content in the seeds of the studied peach kernels was 33–38%. The physical and chemical characteristics of the quality of oils from peach kernels of different varieties are presented. The technology of production of oil from kernels of different varieties of peaches from Odesa and Moldova has been improved, namely, the technological modes of moisture-heat treatment and pressing (Extra Virgin) have been substantiated. It is recommended to carry out the moisture-heat treatment of crushed stone kernels at a temperature of 40–50°C for 15–20 minutes. The most effective pressing mode is the following: load holding time of 3.0 minutes, compression force of 10.0 kN and loading speed of 5.0 kN/cm, the thickness of the pressed pulp under these parameters is 33.0 mm, and the oil yield is about 94.0%. Sensory studies have shown that oil from peach kernels of the ‘Cardinal’ variety has the best average sensory score of 4.9, followed by oil from peach kernels of the ‘Nectarine’ variety with an average score of 4.8, and oil from peach kernels of the ‘Moldavsky’ and ‘Flamingo’ varieties with a sensory score of 4.76 and 4.75, respectively. As a result of the research, it was determined that the fatty acid composition and the ratio of fatty acids practically does not change before and after the technological processing of peach kernels. The content of ω-6 polyunsaturated fatty acids and ω-9 monounsaturated fatty acids in peach kernel oil of the ‘Cardinal’ variety is 95.2% and 98.2% of the original content, respectively, of the ‘Nectarine’ variety – 97.1% and 98.0%, of the ‘Flamingo’ variety – 97.8% and 97.9%, of the ‘Moldavian’ variety – 97.5% and 97.5%.